Archives in a Graph. The Records in Contexts Ontology within the framework of standards and practices of Archival Description - Pierluigi Feliciati (JLIS.it, 2021)
Description is one of the key activities of archival profession, a guarantee for correct management, access and conservation of archives. The cornerstones of the tradition, formalized in the last decade of the twentieth century in the standards of the International Council on Archives, are the respect of fonds and their contexts. The ICA standardization renewal process started in 2012 has produced two versions, both in draft, of the Reference Model of the brand new standard RiC-Records in Contexts, on which the very recent RiC-Ontology has been based. The descriptive hierarchy and the concept of the finding aid – even electronic – as a document isolated from the Linked Open Data available in the infosphere are overcome. This contribution aims to present RiC-CM and RiC-O, their criticalities and perspectives, contextualizing them within the debate and practices of archival description.